Development of a Virus-Based Reporter System for Functional Analysis of Plant rRNA Gene Promoter - Xu, Li; Li, Zhiying; Wang, Sheng (Frontiers in Microbiology, 2021)
Reporter gene-based expression systems have been intensively used in plants for monitoring the activity of gene promoters. However, rRNA transcripts are unable to efficiently express a reporter gene due to a lack of a 5' cap. Because of this obstacle, plant rRNA gene promoters are less well characterized to this day. We developed a virus-based reporter system to characterize the Nicotiana benthamiana rRNA (NbrRNA) gene promoter. The system utilizes the cap-independent translation strategy of viral genomic mRNA and uses the virus-expressed green fluorescent protein (GFP) as an indicator of the rRNA gene promoter activity in virus-infected plants. Based on the reporter system, some characteristics of the N. benthamiana rRNA gene promoter were revealed. The results showed that the strength of the NbrRNA gene promoter was lower than that of the cauliflower mosaic virus (CaMV) 35S promoter, a well-characterized polymerase II promoter. The sequences between −77 and +42 are sufficient for the NbrRNA gene promoter-mediated transcription and the NbrRNA gene promoter may lack the functional upstream control element (UCE). Interestingly, NbrRNA gene promoter activity was increased when the 35S enhancer was introduced. An intron-excision mediated assay revealed that the NbrRNA gene promoter can be inefficiently used by RNA polymerase II in N. benthamiana cells. This virus-based reporter system is easier to operate and more convenient when compared with the previously Pol I promoter assays. And it offers a promising solution to analyzing the functional architecture of plant rRNA gene promoter.